The Impact of Talent Management on Employee Performance: A Perspective from Islamic Banking Industry - Ardyansyah, Farid; Faliza, Nur; Fadhlan, Abdi (SAFE-Network, 2025)
This study aims to examine the impact of talent management practices on employee performance in the Islamic banking industry in East Java, Indonesia. Using a quantitative approach, data were collected through questionnaires distributed to 210 employees of Islamic banks. This study employed multiple regression analysis to test the relationship between talent management practices and employee performance. The results revealed that talent management practices, including recruitment, training, career development, and retention, have a significant positive impact on employee performance. These findings provide insight that effective talent management can improve productivity, work quality, and employee commitment to the organization. Therefore, Islamic banks are recommended to continue investing in talent management as a strategic tool to enhance employee performance, while ensuring these practices align with Sharia values to create an ethical and sustainable work environment.